Employee Green Values: A Review of Theory and Application to Company - Gifari, Dikri; Sanusi, Fauji (Journal of Applied Business, Taxation and Economics Research, 2025)
Abstract: In the rapidly evolving landscape of environmental sustainability, "Green Values" have gained significant traction in the corporate world, reflecting the growing importance of fostering an environmentally conscious workforce. This paper delves into the concept of Employee Green Values (EGVs), which refers to the environmentally friendly beliefs, attitudes, and behaviors exhibited by employees in an organization. Grounded in environmental psychology, the study explores the factors shaping individuals' pro-environmental attitudes, such as personal values, social norms, and situational influences. The research highlights the pivotal role of organizational culture and Green Human Resource Management (GHRM) practices in shaping EGVs. Practices such as green recruitment, training, and performance management foster a psychological green climate, promoting environmentally responsible behaviors among employees. The integration of GHRM practices has been shown to enhance organizational environmental performance and employee engagement, leading to tangible benefits such as improved brand reputation and financial performance. This paper employs a qualitative research methodology, analyzing empirical studies and literature from reputable databases to examine the concept and application of EGVs in the business world. The findings suggest that fostering EGVs is crucial for organizational sustainability, driving innovation, and competitive advantage. The study underscores the importance of aligning EGVs with organizational strategies to create a culture of environmental responsibility, ultimately benefiting both the organization and society at large. Future research directions are proposed to further explore the multifaceted impact of EGVs on organizational outcomes and sustainability efforts.